경기도 내 대기 중 다이옥신 분포 특성에 관한 연구 - 허종원(Jong-Won Heo); 민윤기(Yoon-Ki Min); 김동기(Dong-Gi Kim); 최일우(Il-Woo Choi); 김종수(Jong-Soo Kim); 송일석(Il-Seok Song); 이강웅(Gangwoong Lee) (한국대기환경학회지, 2015)
Atmospheric concentrations of polychlorinated dibezo-p-dioxins and furans (PCDD/Fs) were investigated at urban-residential (Group I: Suwon, Guri and Goyang), industrial (Group II: Ansan, Siheung and Bucheon), urban-rural mixed (Group III: Yangju, Pocheon and Dongducheon) and rural regions (Group IV: Yangpyeong) in Gyeonggi-do from February 2012 to November 2012 quarterly. The concentrations of PCDD/Fs ranged from 0.018 to $0.109pgTEQm^{-3}$ in Group I (mean value: $0.061pgTEQm^{-3}$), 0.059 to $0.367pgTEQm^{-3}$ in Group II (mean value: $0.179pgTEQm^{-3}$), 0.072 to $0.836pgTEQm^{-3}$ in Group III (mean value: $0.334pgTEQm^{-3}$) and 0.014 to $0.066pgTEQm^{-3}$ in Group IV (mean value: $0.034pgTEQm^{-3}$), respectively. In spite of the less PCDD/F emission sources than Group II (industrial regions), the level of PCDD/Fs in urban-rural mixed area showed the highest values with high fluctuation. It's likely that the Group III was affected by fugitive emissions such like biomass burning and unregulated open burning. The mean contribution of particle phase to total PCDD/F concentration was above 83% because most of PCDD/F congeners were partitioned into particle phase. We evaluated their gas-to-particles equilibriums with the regression between the particle-gas partition coefficient, $K_P(m^3μg^{-1})$ and corresponding subcooled liquid vapor pressure ($P_L$). The logarithm-$K_P$ of PCDD/Fs was poorly correlated with $P_L$ at low ambient temperature (below $10^{°}C$) and the slope (m) values for log-log plots of the $K_P$ vs. $P_L$ was steeper in the Group 2 and Group 3 than residential area. It implies that the slope values were likely influenced by both the direct emission source of PCDD/Fs and ambient temperature.